Influence of Tumor Burden on Serum Prostate-Specific Antigen in Prostate Cancer Patients Undergoing Radical Prostatectomy - Mandel, Philipp; Hoeh, Benedikt; Preisser, Felix; Wenzel, Mike; Humke, Clara; Welte, Maria-Noemi; Jerrentrup, Inga; Köllermann, Jens; Wild, Peter; Tilki, Derya; Haese, Alexander; Becker, Andreas; et al. (Frontiers in Oncology, 2021)
Objective: We aimed to assess the correlation between serum prostate-specific antigen (PSA) and tumor burden in prostate-cancer (PCa) patients undergoing radical prostatectomy (RP), since estimation of tumor burden is of high value e.g. in men undergoing RP or with biochemical recurrence after RP. Patients and Methods: From 01/2019 to 06/2020, 179 consecutive PCa patients after RP with information on tumor and prostate weight were retrospectively identified from our prospective institutional RP database. Patients with preoperative systemic therapy (n=19), metastases (cM1, n=5) and locally progressed PCa (pT4 or pN1, n=50) were excluded from analyses. Histopathological features, including total weight of the prostate and specific tumor weight were recorded by specialized uro-pathologists. Linear regression models were performed, to evaluate the effect of PSA on tumor burden, measured by tumor weight after adjustment for patient and tumor characteristics. Results: Overall, median preoperative PSA was 7.0 ng/ml (interquartile range [IQR]: 5.41-10) and median age at surgery was 66 years (IQR: 61-71). Median prostate weight was 34 g (IQR: 26-46) and median tumor weight was 3.7 g (IQR: 1.8-7.1), respectively. In multivariable linear regression analysis after adjustment for patients and tumor characteristics, a significant, positive correlation could be detected between preoperative PSA and tumor weight (coefficient [coef.]: 0.37, CI: 0.15-0.6, p=0.001), indicating a robust increase in PSA of almost 0.4ng/ml per 1g tumor weight. Conclusion: Preoperative PSA was significantly correlated with tumor weight in PCa patients undergoing RP, with an increase in PSA of almost 0.4ng/ml per 1g tumor weight. This might help to estimate both tumor burden before undergoing RP and in case of biochemical recurrence.